Multiplexed therapeutic drug monitoring of antipsychotics in dried plasma spots by LC‐MS/MS. Issue 8 (17th March 2020) - Ruggiero, Carla; Ramirez, Stefania; Ramazzotti, Eric; Mancini, Rita; Muratori, Roberto; Raggi, Maria Augusta; Conti, Matteo
Abstract: In this work, a convenient method for the therapeutic monitoring of seven common antipsychotic drugs in "dried plasma spot" samples has been developed. It is based on the liquid chromatography tandem mass spectrometry technique, operating in multiple reaction monitoring mode, and a straightforward procedure for the simultaneous extraction of all antipsychotics in a single step, with high extraction yield. The method was fully validated with proper accuracy, precision, selectivity and sensitivity, for all the drugs. Limits of quantification were 0.12, 1.09, 1.46, 1.47, 5.70, 1.32, 1.33 µg/L for haloperidol, aripiprazole, olanzapine, quetiapine, clozapine, risperidone, and paliperidone, respectively. Accuracy, intra‐ and interday precision values were <10% for all drugs at all concentration levels examined. The method was tested in the analysis of 30 plasma samples from real patients for each drug. The proposed analytical approach, by combining practical and logistical advantages of microsampling with liquid chromatography tandem mass spectrometry analytical performance, could offer an ideal strategy for accurate and timely therapeutic drug monitoring of antipsychotic drugs in most clinical settings, even in remote centers and/or in out‐patient settings, bringing so many potential improvements in psychiatric patient care.